IDENTIFIKASI ALEL GEN Xa7 PADA PLASMA NUTFAH PADI LOKAL PAREKALIGOLARA MELALUI UJI SEGREGASI FENOTIPE DAN GENOTIPE [Identification of Xa7 Alleles Gene in Landrace Parekaligolara by Phenotype and Genotype Segregation Analysis] - Utami, Dwinita W; Kadir, TS; Nasution, A (BERITA BIOLOGI, 2012)
Bacterial Leaves Blight (BLB) is one of the major diseases in rice. Among the disease resistance genes HDB, Xa7 gene still can compensate the diversity of Indonesian BLB pathogen in the field. One of the local rice germplasm, Parekaligolara (Indica, IRN: 1541) were selected based on allele mining research which contained a Xa7 alleles. The purpose of this study is to identify the alleles of the Xa7 gene contained in Indonesian local rice Parekaligolara germplasm in rice through the segregation testing based on phenotype and genotype performance of segregating population derived from the crossed with the susceptible control varieties, TN1. The segregation testing were conducted in F1 and F2 populations and analyzed on phenotypes of BLB resistance and genotypes using Xa7SNP markers. The analysis results showed that the Xa7 allele variation founded in the Parekaligolara germplasm are act as dominant alleles that contribute on the BLB resistance trait particularly to Race VIII of BLB pathogen. Xa7SNP8 is polymorphic markers for Xa7 alleles gene that are found in Parekaligolara. This marker could be used as a marker assisted for selection, if Parekaligolaras Xa7 alleles will use as a parent in the BLB disease resistant rice breeding program.